PENENTUAN MODEL DAN PENGUKURAN KINERJA SISTEM PELAYANAN PT. BANK NEGARA INDONESIA (PERSERO) Tbk. KANTOR LAYANAN TEMBALANG - Masfuhurrizqi Iman; Sugito Sugito; Dwi Ispriyanti (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2014)
PT. Bank Negara Indonesia (Persero) Tbk. Tembalang Services Office is a provider of service facilities engaged in the financial sector. As a service facilities provider, queue problem is a problem that occurs absolute and must be considered. The queuing situation occurs because the number of customers in a service facility that exceeds the capacity available to perform such services. At PT. Bank Negara Indonesia (Persero) Tbk. Tembalang Services Office, the queue occurs both at the Teller and Customer Service. After analysis, the best model of a queuing system at the Teller is (M/M/3):(GD:∞:∞), while the best model of queuing system in the Customer Service section is (M/M/2):(GD:∞:∞). The model can be concluded that the queue system available in PT. Bank Negara Indonesia (Persero) Tbk. Tembalang Services office is optimal. Keywords : PT. Bank Negara Indonesia (Persero) Tbk. Tembalang Services Office, queuing system, Teller, Customer Service